The Design and Implementation of a Smartphone App to Teach English Language Components and Its Effect on EFL Learners’ Achievement Motivation - Gordani, Yahya; Khajavi, Yaser (AJELP: Asian Journal of English Language and Pedagogy, 2022)
The researchers applied a smartphone e-learning app run on the Android operating systemto teach English vocabulary and grammar and investigated its effectiveness in boosting motivation among English as Foreign Language (EFL) learners. The app was designed via Java programming tools and the Android development environment. To test the app’s effectiveness, sixtyupper-intermediate EFL learners were selected to participate in the study. The participants were then randomly assigned to an experimental and a control group. At first, the participants in the two groups were administered a questionnaire on their achievement motivation. This was followed by twenty sessions of instruction based on the developed app for the experimental group, the traditional teaching practice by a teacher, and the textbook for the control group. After the instruction, the post-test of achievement motivation was administered to both groups. The Mann-Whitney U test showed that integrating the app in EFL classes can significantly affect the mastery and performance types of achievement motivation among language learners.